Aterosklerotik Koroner Arter Hastalığı ve Koroner Kollateral Dolaşımın Klinik Önemi - Çapar, Gazi; Güler, Yeliz; Akgün, Hüseyin; İbişoğlu, Ersin; İnci, Yusuf; Göksu, Muhammed Mert; Üredi, Günseli; Genç, Ömer; Yıldız, Ufuk; Acar, Gamze; Şen, Furkan; Nail Bilen, Mehmet; et al. (2024)
-